Challenges of Novice Language Teachers in Bilingual Schools - Pérez, Celso; López, Maricela; Rivera, Eliphelet; Castillo, María (CIEX JOURNAL, 2016)
This study explores the challenges that novice language teachers, graduated from the Licenciatura en Lenguas Modernas (LEMO) of the Benemérita Universidad Autónoma de Puebla, encounter in bilingual schools. The data was collected by applying interviews to teachers and employers. Findings suggest that some of the most important challenges of those novice teachers are in the scope of the level of the language and the teaching skills; so they suggest reviewing the curriculum and include subject matters related to bilingual education, and provide more practice so that students can perform well in bilingual educational contexts.